Conditional Impact of Institutions on Output Growth_ does the level of institutions differ systematically with the level of development? - Shvechikov, Ivan; Klosová, Anna, 1942-; Taušer, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The institutional quality concept, advanced by academic literature as a mean to enhance output growth, suffer from the absence of a clear implementation strategy. Considering that developing countries usually lack resources to be able to afford large-scale universal institutional reforms, the lack of roadmap puts substantial obstacles to practical application of the given concept. This thesis therefore goes beyond the simple statement of institutional primacy and sets an objective to differentiate the institutional effects relative to the level of development. To test it empirically, fixed effects model is chosen and interaction terms between the measures of institutional quality and the share of middle class are employed. Obtained coefficients indicate that institutions promote economic growth only when middle class share exceeds 25%. At the same time, different aspects of institutional quality exhibit contradictory dynamics. The control of corruption becomes growth enhancing only when middle class constitutes over one third of the population, while the relevance of government effectiveness for economic growth on the contrary decreases with the enlargement of middle class. These findings confirm the presence of conditionality and deny the existence of universal recipe for institutional reforms. Implementation of better institutions based on context-specific approach would therefore bring greater results in terms of economic growth than the direct adoption of best-practice institutions, so intensively advanced by the World Bank and the IMF.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses